EFEITO DO ÓLEO MICROENCAPSULADO DAS AMÊNDOAS DO BACURI (Attalea phalerata (Mart.) ex Spreng.) E DO EXERCÍCIO AERÓBICO EM PARÂMETROS FÍSICOS E BIOQUÍMICOS DE RATOS WISTAR - IARA PENZO BARBOSA (2024)
The almonds of the bacuri fruit (Attalea phalerata (Mart.) ex Spreng.) have been a subject of research due to their functional properties and the presence of bioactive compounds, which are better preserved through the microencapsulation process. The objective of this study was to verify the effect of supplementation with Microencapsulated Oil from Bacuri almonds (OMB) on physical and biochemical parameters of Wistar rats submitted to aerobic exercise. The diets were prepared in accordance with AIN-93 M specifications, replacing soybean oil with OMB. Thirty-two adults male Wistar rats were used, divided into groups: G1 (C-S): AIN93-M sedentary; G2 (OMB-S): AIN93-M with sedentary OMB; G3 (C-EX): AIN93-M exercised; and G4 (OMB-EX): AIN93-M with OMB exercised, and submitted to aerobic training on a treadmill for 8 weeks. The animals' body composition, food consumption and biochemical parameters were verified. The results show that OMB is rich in medium chain fatty acids (MCFA), that weight gain was lower in the OMB-EX group compared to the C-S group (p<0.05), the weight of total visceral fat and the visceral adiposity index were lower in the C-EX group compared to the C-S group (p<0.05). Serum triglycerides were lower in the C-EX and OMB-EX groups compared to OMB-S (p<0.05), final HDL in the OMB-EX group was higher than the initial one. To conclude, the possible synergistic effect of using OMB, rich in AGCM, and the practice of aerobic physical exercises in improving sessions related to body composition and biochemical parameters of triglycerides and HDL stands out.